Inovasi Sektor Publik Melalui Kunjungan Rumah Cageur Jasa Dalam Meningkatkan Kualitas Pelayanan Kesehatan Di Puskemas Gembor Kota Tangerang - Octavia Nur Rahmawati; TB. Yudi Muhtadi; Yusmedi Yusuf (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The Tangerang City Health Office launched the Cageur Jasa innovation as a response to health problems in the area. The purpose of this innovation is to analyze the level of community satisfaction, increase public awareness and behavior in creating healthy families at the Gembor Health Center. This research is a type of qualitative descriptive research using data collection methods through observation, in-depth interviews, and documentation. Public Sector Innovation Theory according to Funglsang & Perdesen (2011) which consists of 6 indicators namely, Technology, Service, Organization, Process, Marketing, and Conceptual. As well as the Quality of Public Services according to Kotler in Arni Purwani and Rahma Wahdiniwaty (2017: 65) which consists of 5 indicators namely, Reliability, Responsiveness, Assurances, Empathy, Tangibles, used as a theoretical framework. The results of the research show that the innovation process at the technology, process, and marketing stages is not optimal, and there are still problems in its implementation. Achievement of goals, integration and adaptation of Cageur Jasa's innovations have also not been maximized in increasing people's satisfaction, awareness and behavior in achieving healthy families. Supporting and inhibiting factors play an important role in the implementation of this innovation. In conclusion, the innovation process has not been maximal in increasing people's satisfaction, awareness, and behavior. Supporting and inhibiting factors also influence the implementation of Cageur Jasa innovations.